Study guides

☆☆

Q: How do you factor 9x squared plus 12x plus 4 - y squared?

Write your answer...

Submit

Still have questions?

Related questions

9x2...I guess that means 9x squared ? The problem: 9x(squared)+12x+4 Here's the answer: (3x+2)(3x+2) or even more simplified: (3x+2) squared

9x(x2+3x-10)

-9x 2 -12x+5 =

Type your answer here... 81

9x + 2 = 12x + 14 -3x = 12 x = -4

(x+1)(x+8)

3(x2 + 3x + 1)

9x2 + 8x - 1 = (9x - 1)(x + 1)

That doesn't factor neatly. Applying the quadratic equation, we find two real solutions: (-2 plus or minus the square root of 5) divided by 3x = 0.07868932583326327x = -1.4120226591665965

(9x)2 +9x/(45x)2 +81= 9+9x/86

You don't need to factor that; you can add them together, since they have the same variable.However, assuming you might mean 81x squared + 9x, you can take out the common factor, which is 9x.

x2 - 9x + 8 = (x-1)(x-8)

(2x+3)(x+3)

9x squared plus 16 = 0 factored is plus and minus 4/3 i.

12x + 131 = 189 + 3x 12x - 3x + 131 - 189 = 0 9x - 58 = 0 9x = 58 x = 6,44444

x2-9x+8=0 has two solutions:x = 8x = 1

Step 1: Divide by 9x: 9x (x2 + 3x - 10) = 9x(x + 5)(x - 2)

x(x^2 + 2x + 9)

9x squared plus 16 = 0 factored is plus and minus 4/3 i.

12x + 17 - (9x - 2)Eliminate parentheses:12x + 17 - 9x + 2Combine the 'x' terms:3x +17 + 2Combine the numerical terms:3x + 19

(x + 12)(x - 3)

3(2x - 3)(x + 3)

Since the problem has 4 terms, first you factor x cubed plus 9x squared, then you factor 2x plus 18. So when you factor the first two term, you would get x sqaured (x plus 9). Then when you factor the last two terms and you get 2 (x plus 9). Ypure final answer would be (x squared plus 2)(x plus 9)

x2-9x can be factored by taking x out of each term x(x-9)

the answer is (3x-2)(9x squared+6x+4)